Coronary Arteriovenous Fistula Secondary to Percutaneous Coronary Intervention of Chronic Total Occlusion - Seshasayee Narasimhan (Case Reports in Vascular Medicine)
This is a case report of a 61-year-old female presenting with ongoing chest pain in the setting of an NSTEMI with lateral ST-T changes. On attempting to open the left circumflex (LCX), it resulted in a proximal LCX dissection. The patient remained stable with no further chest pain. She was treated with IV Eptifibatide for 48 hours and restudied in 72 hours. Repeat coronary angiography showed a marginally improved proximal dissection plane with a coronary AV fistula. She was managed conservatively and discharged with a non-invasive assessment in 8 weeks. The patient had a negative stress echocardiogram and was managed with maximal medical therapy.